Immobilization and Purification of Enzymes With the Novel Affinity Tag ChBD-AB From Chitinolyticbacter meiyuanensis SYBC-H1 - Zhou, Jie; Chen, Jianhao; Zhuang, Nisha; Zhang, Alei; Chen, Kequan; Xu, Ning; Xin, Fengxue; Zhang, Wenming; Dong, Weiliang; Jiang, Min (Frontiers in Bioengineering and Biotechnology, 2020)
A new protein immobilization and purification system has been developed based on the improved plasmid vectors, designated pETChBD-X, which contained the gene coding for two novel chitin-binding domains ChBD-AB, factor Xa cleavage site and adapted for gene fusions. The ChBD-AD from Chitinolyticbacter meiyuanensis SYBC-H1 was used as a novel affinity tag to anchor fusion proteins to chitin granules. The granules carrying the ChBD-AD fusion proteins can be isolated by a simple centrifugation step and used directly for some applications. Moreover, when required, a practically pure preparation of the soluble recombination protein can be obtained after Factor Xa cleavage. The efficiency of this system has been demonstrated by reaching 95% of protein absorbed to chitin within 30 min and recycling over 75% of interest protein after Factor Xa cleavage to separate interest protein and fusion tag. Furthermore, 65% L-glutamate oxidase with this fusion tag could be purified and immobilized within only one step and to be reused in converting L-glutamate to ɑ-ketoglutaric acid directly, the average conversion rate kept above 65% even within four batches of enzyme conversion reaction.